Implementing FAST Method on the Development of Object-Oriented Cooperative Information Systems - Meri Azmi; Yance Sonatha; Ervan Asri; - Rasyidah; Dwi Sudarno Putra (Society of Visual Informatics, 2018)
Cooperative is one form of businesses that is widely known as people concern and has a legal entity. In helping its members, the cooperative embraces familial value principle and mutual cooperation for the common social welfare. In carrying out its duties and functions, the cooperative requires an accurate and accountable recording. However, currently there are still many cooperatives performing their recording manually. Therefore, an information systems is needed in assisting the cooperative management in term of this recording. This research developed an object-oriented cooperative information systems using FAST method. Its purpose is to develop a cooperative information systems that can facilitate itsÂ administrators in order to record the data through information systems-based, so the inaccuracy in recording, and loss of important data and archives can be avoided. Its result is a system that has been implemented into a cooperative. Hence, the information systems is developed using Java Programming language and MySQL database. From the system testing results shows that this information systems is capable in processing the accounting data associated with savings and loan transactions automatically, and produce information in the form of managerial and financial reports.